Songwriting: research, theory, methods, and practice. (1st June 2016) - Baker, Felicity; Robb, Sheri; Clement-Cortes, Amy; Silverman, Michael; Krüger, Viggo; Short, Helen; Murphy, Kathleen
Abstract : Background : This round table brings together academics with research expertise in songwriting to share their most contemporary research and practice. Objective : To report on developments in theory, models, methods, and practices in the use of songwriting with children in hospital and community settings, in palliative care, and in mental health. Methods : Five academics will present their research findings on the following topics: models of therapeutic songwriting derived from a series of research studies (Baker); strategies to increase engagement in the songwriting process (Robb); the use of songwriting to facilitate relationship completion at end of life (Cortes); single-session songwriting approaches in acute mental health inpatient settings (Silverman); songwriting approaches in school settings to enhance engagement with learning (Kruger); rap lyric writing from a psychodynamic perspective (Short); songwriting in early recovery from substance dependence – incorporating the 12 step tradition (Murphy). Discussion : We will explore the similarities and differences in concepts, theories, and approaches that emerge from the presentations. Conclusions : Songwriting has matured as a music therapy intervention with a diverse range of uses, methods, and outcomes.